ROLE OF MODERN MARKETING STRATEGIES IN TOURISM DEVELOPMENT (Marketing Journal, 2025)
The article examines the role of modern marketing strategies in tourism development from a theoretical perspective. Mechanisms of demand formation in tourism services are analyzed through digital marketing, branding, artificial intelligence, AR/VR technolo gies, and psychological approaches. It is demonstrated how marketing strategies influence the perception of value and competitiveness of tourism destinations. A conceptual model of marketing integration in the tourism sector is proposed. Theoretical insigh ts are substantiated based on a review of current academic literature.
Keywords: tourism marketing; digital strategies; branding; artificial intelligence; customer loyalty; destination management